PHYSICAL ACTIVITY AS A CHALLENGE OF MODERN TIMES - SELECTED ISSUES (Physical Culture and Sport: Scientific Perspective, 2024)
In the ontological sense, modernity is a way of existence of someone or something. Modernity in the praxeological sense is a branch of scientific research that deals with the methods of all purposeful human action. Modernity in the axiological sense is the science of values. If physical activity is subjected to in-depth research and analysis, it is characterized by a clear dualism in the ontological sense, which is a consequence of needs. On the one hand, physical activity improves a person's physical condition and strengthens the body, and on the other hand, it causes the growth and regeneration of neurons, which improves intellectual processes, that is, a person's perception. Only a combination of physical activity and learning can bring the expected educational results at any level of education. In pragmatic terms, the clearly defined goal of physical activity is the sports performance of an individual or team. This often leads to the use of training methods or assisted by external products, i.e. chemical agents, as well as medical and nutritional products that use biological forms, such as blood transfusions, among others. The effects are as follows: from an axiological point of view, physical activity directs action to the exclusion of all other values except success. Success creates reality, is generated by interdisciplinary issues with the possibility of violating human health in the name of the idea of winning above all else. Such success can lead to the dehumanization of sports and the dehumanization of human beings. The concept of humanism and fair play is gradually lost. The above questions form the basis of the investigation, which becomes a research challenge.
Keywords: physical activity; sports; dehumanization of sports life